Neuroprotection Against Oxidative Stress: Phytochemicals Targeting TrkB Signaling and the Nrf2-ARE Antioxidant System - Hannan, Md. Abdul; Dash, Raju; Sohag, Abdullah Al Mamun; Haque, Md. Nazmul; Moon, Il Soo (Frontiers in Molecular Neuroscience, 2020)
Oxidative stress (OS) plays a critical role in the pathophysiology of several brain-related disorders, including neurodegenerative diseases and ischemic stroke, which are the major causes of dementia. The Nrf2-ARE (nuclear factor erythroid-2-related factor 2 (Nrf2)/antioxidant responsive element (ARE) antioxidant) system, the primary cellular defense against OS, plays an essential role in neuroprotection by regulating the expressions of antioxidant molecules and enzymes. However, simultaneous events resulting in the overproduction of reactive oxygen species (ROS) and deregulation of the Nrf2-ARE system damage essential cell components and cause loss of neuron structural and functional integrity. On the other hand, TrkB (tropomyosin-related kinase B) signaling, a classical neurotrophin signaling pathway, regulates neuronal survival and synaptic plasticity, which play pivotal roles in memory and cognition. Also, TrkB signaling, specifically the TrkB/PI3K/Akt (TrkB-phosphatidylinositol 3 kinase/protein kinase B) pathway promotes the activation and nuclear translocation of Nrf2, and thus, confers neuroprotection against OS. However, the TrkB signaling pathway is also known to be downregulated in brain disorders due to a lack of neurotrophin support. Therefore, activations of TrkB and the Nrf2-ARE signaling system offer a potential approach to the design of novel therapeutic agents for brain disorders. Here, we briefly overview the development of OS and the association between OS and the pathogenesis of neurodegenerative diseases and brain injury. We propose the cellular antioxidant defense and TrkB signaling-mediated cell survival systems be considered pharmacological targets for the treatment of neurodegenerative diseases, and review the literature on the neuroprotective effects of phytochemicals that can co-activate these neuronal defense systems.